2020
DOI: 10.3390/ijerph17030999
|View full text |Cite
|
Sign up to set email alerts
|

School-based Physical Activity Interventions in Children and Adolescents: A Systematic Review

Abstract: Background: The aim of this systematic review was to examinemotivational interventions based on physical activity as precursor of psychosocial benefits inside of the scholar context. Method: studies were identified in seven databases (Web of Science, Sport Discuss, Scopus, Eric, Pubmed, Psycinfo and Google Scholar). The search process was from June 2011 to September 2019. A total of 41 articles met the inclusion criteria. Results: 23 studies showed psychological effects after intervention and also 10 studies s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 74 publications
(395 reference statements)
5
48
0
4
Order By: Relevance
“…It is well-established that physical activity (PA) during education time can be beneficial for children's academic performance (Beck et al, 2016;Donnelly et al, 2016;Watson et al, 2017;Mullender-Wijnsma et al, 2019;Norris et al, 2019;Vaquero-Solis et al, 2020). Moreover, it was recognized that schools should find more opportunities for increased PA within the elementary school day for many health benefits (Mendo-Lazaro et al, 2017;Bartholomew et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is well-established that physical activity (PA) during education time can be beneficial for children's academic performance (Beck et al, 2016;Donnelly et al, 2016;Watson et al, 2017;Mullender-Wijnsma et al, 2019;Norris et al, 2019;Vaquero-Solis et al, 2020). Moreover, it was recognized that schools should find more opportunities for increased PA within the elementary school day for many health benefits (Mendo-Lazaro et al, 2017;Bartholomew et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There are many previous [17,26,46,47,60] studies that have shown the positive effect of PA and the promotion of health-related habits in adolescents. However, as mentioned above, none of them took into account the individuals' heterogeneity [25].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, given that a random sampling of the schools is carried out, the sample schools will choose from socio-demographically diverse areas. Moreover, the systematic review conducted by Vaquero-Solís et al [25] identified that more intervention studies based on SDT are necessary in order to assess the effects on variables over time (more than 3 months).…”
Section: Justification Of Duration Volume Frequency Type Pa and Lomentioning
confidence: 99%
See 2 more Smart Citations